Mentoring and Protege Development among Cataloguers in Selected University Libraries in Nigeria - Ogunlana; Okunoye; Ajani (Indian Journal of Information Sources and Services, 2013)
This study investigated the mentoring relationship among cataloguers in selected university libraries in Ogun State, Nigeria. Data were collected via questionnaire from all the librarians working in cataloguing section of the selected university libraries. Results of the analysis showed that mentoring plays significant role in the protégé career development; there exist relationship between mentor and protégé attitude, between mentoring methods and perceived success. These finding were discussed with reference to relevant literature with their implications for both the mentors and protégé. The recommended that senior cataloguers need to put new and young cataloguers on the right path so that negative attitude, perception should be reduced, the mentee should understand that the mentoring relationship is about advancing his/her professional skills and knowledge, and meeting agreed upon professional goals, thus they should demonstrate commitment and both mentors and protégé need to work at the mentoring relationship and the mentoring process.